Quantum transport through MoS2 constrictions defined by photodoping. (20th April 2018) - Epping, Alexander; Banszerus, Luca; Güttinger, Johannes; Krückeberg, Luisa; Watanabe, Kenji; Taniguchi, Takashi; Hassler, Fabian; Beschoten, Bernd; Stampfer, Christoph
Abstract: We present a device scheme to explore mesoscopic transport through molybdenum disulfide (MoS2 ) constrictions using photodoping. The devices are based on van-der-Waals heterostructures where few-layer MoS2 flakes are partially encapsulated by hexagonal boron nitride (hBN) and covered by a few-layer graphene flake to fabricate electrical contacts. Since the as-fabricated devices are insulating at low temperatures, we use photo-induced remote doping in the hBN substrate to create free charge carriers in the MoS2 layer. On top of the device, we place additional metal structures, which define the shape of the constriction and act as shadow masks during photodoping of the underlying MoS2 /hBN heterostructure. Low temperature two- and four-terminal transport measurements show evidence of quantum confinement effects.